Modeling Informality Formally: Households and Firms - Galiani, Sebastián (2012)
Informality is widespread in most developing countries. In Latin America, 50% of salaried employees work informally. Three stylized facts characterize informality: (1) small firms tend to operate informally while large firms tend to operate formally; (2) unskilled workers tend to be informal while skilled ones have formal jobs; (3) ceteris paribus, secondary workers (a worker other than the household head) are less likely to operate formally than primary workers. We develop a model that accounts for all these facts. In our model, both heterogeneous firms and workers have preferences over the sector they operate and choose optimally whether to function formally or informally. There are two labor markets, one formal and the other informal, and both firms and workers act unconstrained in them. By contrast, a prominent feature of the preexisting literature is that workers' decisions play no role in determining the equilibrium of the economy. In our model, policies that reduce the supply of workers in the informal labor market at given wages will increase the level of formality in the economy. This has noteworthy implications for the design of social programs in developing countries. We also show that an increase in the participation of secondary workers would tend to raise the level of informality in the economy.